Extradural abscess following synthetic fabric duraplasty - Sapkota, Shabal (Surg Neurol Int, 2021)
BACKGROUND: Duraplasty refers to the neurosurgical process of reconstructing dural defect. Variety of materials is used for such reconstruction, including natural, semisynthetic, and synthetic materials. Although synthetic materials are readily available and easy to apply, these are associated with foreign body reaction which may lead to serious consequences in some cases. We describe one such rare instance of extradural abscess after polypropylene synthetic fabric duraplasty. CASE DESCRIPTION: Our patient is a 33-year-old lady who suffered road traffic accident leading to massive brain laceration, contusion of bilateral frontal lobes, and anterior skull base fractures. Emergency craniotomy was carried out and dural defect repaired with polypropylene (G-Patch; G. Surgiwear(®) Ltd.) synthetic fabric as the duraplasty material. Three months later, the patient presented with discharging wound at the incision site. Neuroimaging showed ring enhancing lesion in frontobasal extradural space with cutaneous extension. The lesion failed to heal despite intravenous antibiotics and surgery was planned. Intraoperatively, abscess was found between G-Patch and dura. Histopathology showed granulomatous foreign body reaction. The lesion healed after synthetic dura removal and abscess drainage. CONCLUSION: Although various materials are used for duraplasty, there is no clear consensus on what material should be used for dural repair. Synthetic materials are bio-inert, offer good handling and malleability. Polypropylene has been used safely for both single- and double-layered duraplasty. However, foreign body reaction may occur and very rarely present as extradural abscess. Randomized trials should be done to establish the safety and efficacy profile of commonly used duraplasty materials.